Effect of Triclabendazole and Dexamethasone on Ovine Fascioliasis: Farouk J. Khalil1; Huda F. Hasan2 ; Oday. K. Luaibi3 and Khaled. J. Khalil4 - Luaibi, Oday K. (The Iraqi Journal of Veterinary Medicine, 2013)
Thirty sheep in a flock suffering from fascioliasis were selected for the trial . Clinical findings, hematological, biochemical and fecal investigations were conducted. These animals were equally divided into two groups, the 1st group was given the flukecide triclabendazole alone, at a rate of 12mg/kg body weight orally and the 2nd group was given the same dose orally together with dexamethasone at a rate 0.5 mg / kg body weight I/M. Results showed that the 2nd group gave the quickest and the best response in the treatment. This could be explained that the use of corticosteroid assisted the triclabendazole in preventing immune damage and fibroplasias inflicted by the liver flukes beside to improvement metabolic actions of the animal.